Pragmastylistic Aspects of Phraseological Units in English and Uzbek Media Texts (Journal of Science-Innovative Research in Uzbekistan, 2025)
This study explores the pragmastylistic aspects of phraseological units in English and Uzbek media texts, focusing on their role in shaping communicative intent, stylistic effects, and cultural nuances. Phraseological units, as fixed expressions with idiomatic meanings, serve as powerful tools in media discourse to convey emotions, persuade audiences, and reflect cultural identities. By analyzing a corpus of contemporary English and Uzbek media texts, this research examines how these units function pragmatically to achieve rhetorical goals and stylistically to enhance expressiveness. The comparative analysis highlights similarities and differences in the use of phraseological units, revealing how linguistic and cultural contexts influence their application. The findings underscore the importance of phraseological units in media texts as markers of stylistic creativity and pragmatic effectiveness, offering insights into cross-linguistic and cross-cultural communication.